Endotracheal Tube Cuff Pressures and Incidence of Postoperative Sore Throat - Khatun, U H Shahera (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Abstract not available J Bangladesh Coll Phys Surg 2024; 42: 4-5